The oblique anticausative in Lithuanian - Bjarnadóttir, Valgerður (Baltistica, 2014)
This article examines Lithuanian structures with accusative functioning as a subject. It pursues the idea that this accusative is of old origin. This hypothesis is based on a detailed comparison with Old Icelandic, revealing striking similarities within an unproductive semantic group, denoting force of nature and meteorological phenomena. Another semantic group, denoting physical inconveniences, highly productive in Lithuanian, shows signs of individual developments. Furthermore, I will propose that the structures under investigation will be labelled oblique anticausatives as they show an alternation pattern similar to other “normal” anticausatives only with an oblique case-preserving anticausative strategy, used to express an uncontrolled, non-agentive nature of an event, usually brought about by natural force.